Early Childhood Education as an Instrument for Good Governance in Cameroon - Nkemleke, Amshetu Melo Forchu (Journal of Innovation in Education and Social Research, 2024)
This study examined Early Childhood education as an instrument for good governance in the entire World and Cameroon in particular. Good governance, is a situation whereby those in power decides what is to be implemented or not without making the governed feel marginalized. Good governance requires certain characteristics before one can say it is good like accountability, vividness, responsive participatory attributes, effectiveness and efficiency in duties, control, and evaluation of all the due processes of the law as needed. In Cameroon, Early Childhood Education is an education given to children in a formal school setting. It starts from 0-8 years, which means that the child starts from crèche through primary three to acquire this crucial education. Thus, pupils are taught social norms and social skills like friendship, volunteering, sympathy, kindness, empathy, truthfulness, and accountability. It has been observed that most developing nations are experiencing the problem of under-development economically, socially, politically, and morally due to a lack of preschool experience as witnessed in countries with preschool. This problem could be traced to negligence, negative attitude as well as unawareness of the importance of early childhood education in Cameroon. Since good governance is directly related to social and moral habits, good governance cannot be achieved if people being governed are socially and morally undeveloped, due to lack of training in early childhood education. Therefore, the good governance characteristics for future leaders should be imbibed in early childhood education and the a strong community. Hence, there is a need for the government to sensitize the parents and teachers on the importance of preschools to parents to enroll their children in early childhood education and that the state should create preschools all over Cameroon. The cost of preschool most parents are subsistence farmers with low incomes.